2022
DOI: 10.3389/fmicb.2022.1065412
|View full text |Cite
|
Sign up to set email alerts
|

Composition and diversity of soil bacterial communities under identical vegetation along an elevational gradient in Changbai Mountains, China

Abstract: Soil bacteria play important roles in biogeochemical cycling and biodiversity in mountain ecosystems. Past studies have investigated the bacterial community composition and diversity in elevation gradations covered by different vegetation types, but for a better assessment of elevation effects, here we studied bacterial communities in soil under identical vegetation cover. High-throughput amplicon sequencing of the V3-V4 region of bacterial 16S rDNA was used to investigate the diversity and composition bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Needle GS activity increased with elevation, agreeing with a rule that the activity of this enzyme gets upregulated when it needs to strengthen the N uptake and utilization for new production [41,42]. Although soil AN was the only parameter that showed an increasing trend along the elevational gradient, it increased in plots at the elevation of 910-930 m compared to that at the lowest elevation of 870-880 m and remained unchanged with elevation from 910 m. This growing pattern was in agreement with those found along elevational gradients on Ailao mountain [43] and in the Changbai Mountains [44]. Soil NN content was higher at the elevation of 920-930 m than at 870-880 m, which impeded the general change as an increasing trend.…”
Section: N and P Availabilities Along Elevation Gradients For Pinus P...supporting
confidence: 86%
“…Needle GS activity increased with elevation, agreeing with a rule that the activity of this enzyme gets upregulated when it needs to strengthen the N uptake and utilization for new production [41,42]. Although soil AN was the only parameter that showed an increasing trend along the elevational gradient, it increased in plots at the elevation of 910-930 m compared to that at the lowest elevation of 870-880 m and remained unchanged with elevation from 910 m. This growing pattern was in agreement with those found along elevational gradients on Ailao mountain [43] and in the Changbai Mountains [44]. Soil NN content was higher at the elevation of 920-930 m than at 870-880 m, which impeded the general change as an increasing trend.…”
Section: N and P Availabilities Along Elevation Gradients For Pinus P...supporting
confidence: 86%
“…Our results showed that drought and salt stress have different effects on the rhizobacteria alpha diversity. Soil bacterial abundance and diversity are important indicators of soil health and function, and they are influenced by various environmental factors, such as soil pH, moisture, nutrients, and salinity ( Lelana et al., 2022 ; Li et al., 2022a ). In this study, drought significantly decreased the ACE, Chao1 and Simpson indices ( Table 6 ), indicating that drought reduced the abundance and diversity of rhizobacteria community.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the past have confirmed that soil bacteria not only play an essential role in organic matter transformation, nutrient cycling, energy flow, etc., but also have significant impacts on soil sustainability [3]. Soil bacterial communities, as essential components of the soil microbial community, affect biogeochemical cycles and biodiversity in ecosystems [4]. Some bacteria in the soil (such as rhizobia) can form symbiotic relationships with plant roots, helping plants absorb nutrients, promoting plant growth, and enhancing plant resistance to pathogens and adversity [5,6].…”
Section: Introductionmentioning
confidence: 99%